Utilization sugarcane waste (Saccarhum officinarum L.) as a bioetanol basic material through a bioprocess engineering approach based microbes - Mohamad, Danial; Lanti, Syahrul; Dwiyani, Annisa; Matalauni, Citra Leonita; Suduri, Adam (Genbinesia Journal of Biology, 2024)
Sugarcane (Saccharum officinarum L.) is a plant that is able to produce a lot of sugar content in its stem organs. The amount of sugar production from sugar cane, of course, produces and leaves bagasse waste. A number of studies have shown that bagasse waste still contains a lot of important materials, one of which contains lignocellulose substrates that have the potential to be converted into bioethanol raw materials. The purpose of this study is to determine, see and assess the production of bioethanol produced by utilizing sugarcane waste as raw material through a microbial-based bioprocess engineering approach. This research is an experimental type with the treatment of free cells and immobilized cells in bioethanol production by utilizing sugarcane waste as raw material with the stages of processing waste into flour, dried, hydrolyzed, and analyzed sugar content before ethanol production test. Based on the results of research on ethanol testing using free cells, the highest alcohol content was obtained at a concentration of 3% and 4%. For the test of ethanol content using immobilized cells, the highest ethanol content was obtained at a concentration of 4%.